A multi-layer spiking neural network-based approach to bearing fault diagnosis. (September 2022) - Zuo, Lin; Xu, Fengjie; Zhang, Changhua; Xiahou, Tangfan; Liu, Yu
Highlights: A multi-layer spiking neural network (SNN) is proposed for fault diagnosis. The multi-layer SNN is based on the probabilistic spiking response model (PSRM). A multi-layer learning algorithm is developed for network training. The effectiveness of the proposed method is demonstrated via bearing experiments. The multi-layer SNN is biologically transparent for bearing fault patterns. Abstract: Effective fault diagnosis is a crucial way to reduce the occurrence of severe damages of many industrial products. With the increasing amount of condition monitoring data, deep-learning-based methods have become promising ways for intelligent fault diagnosis thanks to their automatic feature extraction capability. Most recently, the third-generation neural network, called spiking neural network (SNN), has been introduced as an effective tool for fault diagnosis. However, the internal state and the error function of neurons in the SNN model cannot satisfy the conditions of continuity and differentiability, resulting in the difficulty of the gradient back-propagation, and it, therefore, prevents the extension of the SNN to a deep manner. In this article, a probabilistic spiking response model (PSRM) with a multi-layer structure is put forth to enhance the performance of the SNN in terms of bearing fault diagnosis. In the PSRM, the extracted features from the local mean decomposition (LMD) method are converted into the probability pulse sequences, and a multi-layer learning algorithm is developed to facilitate the multi-layer network training. The fault diagnosis results from three bearing databases, i.e., CWRU, MFPT, and Paderborn University datasets, demonstrate that the proposed PSRM exceeds a majority of the state-of-the-art machine learning methods. The proposed multi-layer SNN can also provide transparency to different bearing fault patterns by the membrane potentials of the spiking neurons in the output layer.